RENDANG SEBAGAI INSTRUMEN GASTRODIPLOMASI INDONESIA TERHADAP AUSTRALIA (2018-2019) - Uci Dwi Jayati; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This paper aims to analyze about the Indonesian government strategic to improve Indonesia’s image in Australia. In Australia, Indonesia is known as a country full of conflict, undemocratic, and supports separatism. It is caused by the dynamic bilateral relationship between Indonesia and Australia. This condition can threaten the existence of Indonesia in Australia. So, Indonesian government needs a strategy to improve Indonesia's image in the Australia. One way that the Indonesian government does is to implementation culinary diplomacy or known as gastrodiplomacy.This paper uses diplomacy theory, with a domestic level analysis to understand the gastrodiplomacy actions taken by the Indonesian government in influencing the Australian public's perception of Indonesia's image. It is a descriptive qualitative research, with data collection method in the form of library research. The data comes from books, scientific journals, research reports, and scientific articles that can be trusted.The result shows that the Government of Indonesia through the Embassy of the Republic of Indonesia (KBRI), Consulate General of the Republic of Indonesia (KJRI), and the Ministry of Tourism (Kemenpar) have implemented several strategies to increase Indonesia's positive image in Australia. First, Indonesia hold  Indonesian festival in Australia. Second, Idonesian  government presented rendang on diplomatic meetings. Third,Indonesian government working with restaurants owned by the Indonesian diaspora in Australia.Keywords: Australia, gastrodiplomacy, Indonesia, rendang